2013
DOI: 10.1016/j.tjog.2013.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Cervicovaginal secretions protect from human papillomavirus infection: Effects of vaginal douching

Abstract: This study confirms the protective activity of CVSs against HPV infection regardless of age. In this in vitro study, the net effect of douching was found to be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…On the other hand, the relationship between vaginal douching and higher rates of genital infections, including STIs/ HPV, is well documented in the general population [38,39]. Supporting these findings are local immune system disturbance and removal of the cervical mucus protective barrier [40]. In contrast, a study in Cambodia found less HPV infections in FSWs practicing vaginal douching just after sexual intercourse [41].…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, the relationship between vaginal douching and higher rates of genital infections, including STIs/ HPV, is well documented in the general population [38,39]. Supporting these findings are local immune system disturbance and removal of the cervical mucus protective barrier [40]. In contrast, a study in Cambodia found less HPV infections in FSWs practicing vaginal douching just after sexual intercourse [41].…”
Section: Plos Onementioning
confidence: 99%
“…This supposition was supported by an in vitro study showing that washing within 30 minutes after HPV exposure, the approximate amount of time needed for HPV to attach to cells, could prevent 90.0% of HPV infection. 38 Second, most Cambodian FSWs used their fingers for intravaginal washing; very few used a commercial douching device as did US women. Thus, microabrasions of the vaginal epithelium might have occurred less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…5,37 Vaginal douching or wiping may also disturb local innate immunity or remove cervicovaginal mucus secretions that serve as a protective barrier against HPV. 38 Some chemicals used in intravaginal cleansing (e.g., soaps, detergents, or antiseptics) may cause epithelial damage, increase vaginal pH, facilitate bacterial vaginosis, and thus facilitate viral infections. 5 In contrast, intravaginal cleansing, particularly after sexual intercourse, may help to clear the transmitted HPV and reduce infection risk.…”
Section: Introductionmentioning
confidence: 99%